2021
DOI: 10.3389/fpsyt.2021.697783
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions for Healthcare Providers With PTSD in Life-Threatening Pandemic: Systematic Review and Meta-Analysis

Abstract: Objective: This study aims to evaluate the effect of psychological interventions on healthcare providers (HCP) with post-traumatic stress disorder (PTSD) due to their necessary exposure in life-threatening pandemic.Methods: We performed a systematic research on Medline, Embase, Cochrane Central, PsycInfo, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, ProQuest PTSD Pubs ProQuest Dissertations & Theses Global, and other gray databases by January 2021. Randomized controlled trials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To our knowledge, there are no studies that have investigated the effectiveness of the UP to decrease symptoms of post-traumatic stress during COVID-19, and these results show that only by applying a brief UP preventive program was a significant reduction in these severe and disabling symptoms achieved. Regarding other psychological interventions to reduce PTSD symptoms due to COVID-19 experiences, a systematic review found that the most feasible and effective treatment program for healthcare professionals with PTSD is still unclear; however, cognitive behavior therapy and mindfulness-based interventions have shown the most significant effects based on current limited evidence [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are no studies that have investigated the effectiveness of the UP to decrease symptoms of post-traumatic stress during COVID-19, and these results show that only by applying a brief UP preventive program was a significant reduction in these severe and disabling symptoms achieved. Regarding other psychological interventions to reduce PTSD symptoms due to COVID-19 experiences, a systematic review found that the most feasible and effective treatment program for healthcare professionals with PTSD is still unclear; however, cognitive behavior therapy and mindfulness-based interventions have shown the most significant effects based on current limited evidence [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, no pro-gram effectiveness results were published [31]. Systematic reviews of preliminary studies show that interventions focused on building resilience may decrease perceived stress and burnout [32,33] and that cognitive behavior therapy and mindfulness-based interventions may be effective to treat symptoms of posttraumatic stress disorder (PTSD) due to COVID-19 experiences [34].…”
Section: Introductionmentioning
confidence: 99%
“…All the included studies were systematic literature reviews, with six of them involving metaanalysis (Table 1). Only three reviews included RCTs exclusively (20)(21)(22). The included studies covered 47 countries; 27 of them (57%) were high-income countries (HIC), while 11% were low-income countries (LIC) (Figure 2).…”
Section: Characteristics Of the Included Studymentioning
confidence: 99%
“…[25][26][27] Only one previous meta-analysis examined the efficacy of psychological interventions for healthcare professionals with PTSD in a life-threatening pandemic. 28 This review paid more attention to the effectiveness of psychological interventions and included only one study in each meta-analysis. Studies of interventions conducted in healthcare professionals focusing on reducing PTSD symptoms are accumulating, especially amid the COVID-19 pandemic.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Only one previous meta-analysis examined the efficacy of psychological interventions for healthcare professionals with PTSD in a life-threatening pandemic 28. This review paid more attention to the effectiveness of psychological interventions and included only one study in each meta-analysis.…”
Section: Introductionmentioning
confidence: 99%